Model Numerik dan Aplikasi Lapangan pada Peningkatan Daya Dukung Tanah Gambut yang Diperbaiki dengan Pasir serta Fondasi Kayu Plat Bersirip Baja - Stephanus Alexsander; Fatma Sarie; Mohammad Ikhwan Yani; Liliana; Zadya Putra, Muhammad Ryan Febriza (Jurnal Serambi Engineering, 2025)
Building on peat soils often causes problems, one of which is significant settlement. Local people often use wooden foundations on peat soils, but they may not be able to support the load. This study proposes to modify the timber foundation by incorporating steel strip plates and sand amelioration, which will be simulated using software and subjected to laboratory testing to evaluate the effect of incremental loads on settlement. Peat soil samples were collected from Jalan Bukit Raya XIV, Palangka Raya for laboratory analysis of their physical and mechanical properties. Plaxis 2D software was used for the modeling analysis. Field loading continued until settlement reached the SNI 8460: 2017 allowable threshold of 2.5 cm. The soil test results were as follows: moisture content = 580.51%; fiber content = 33.12%; ash content = 4.64%; bulk density = 1.06 g/cm³; specific gravity = 1.79; cohesion = 0.0023 kg/cm²; angle of internal friction = 2°. The software analysis results indicate that modifying the hardwood base with three steel strip plates is the most effective method for load resistance. The load at 2.5 cm settlement is 340 kg from the load test and 350.5 kg from the Plaxis 2D analysis.